Hyraulic canals : - Montanés, José Liria (Taylor & Francis, 2006)
Few up-to-date books exist on the hydraulics of canals, and indeed very few which deal with the design, construction, management and modernization of canals. This new book is written for engineers with a good grounding in hydraulic engineering who want a practical reference and guide. It provides in-depth study of the problems of losses caused by seepage, the various possible linings, the constraints posed by the construction of a canal without a lining and the relevant methods of calculation. It also explores the calculation of the various structures inserted in the canal, notably the gates. Proper management of is essential in order to avoid losses from spillage. Current mathematical models are presented for studying the influence on the movements of a canal exerted by the variations in the opening of the gates or modifications in the rates of flow. The rehabilitation and modernization of old canals which are still in service are considered, and methods of avoiding deterioration by effective maintenance and conservation are addressed.